Hollow Core Antiresonant Fiber With Radially Asymmetric Nodeless Claddings - Tao-Ying Yu; Xuesong Liu; Zhong-Wei Fan (IEEE Photonics Journal)
We propose and numerically study a novel type of hollow core antiresonant fiber with a single layer of nodeless radially asymmetric cladding tubes, i.e., the cladding tube presents a bulb-like shape, that the local cladding curvature radius at the core/cladding boundary is larger than the other side. Compared with counterparts with conventionally used radially symmetric nodeless claddings, e.g., circular and elliptical tubes, numerical analysis shows that such structure can provide excellent broadband low-loss property and robust single-mode guidance. By tuning the local cladding tube curvature radius, the confinement loss characteristic can be less sensitive but the phase matching between core high-order modes (HOMs) and resonant cladding modes can be significantly enhanced than that of the elliptical structure. Since the cladding modal fields are moved closer to those of the core HOMs, the HOM extinction ratio can reach above 104 and maintain over an octave of bandwidth.